Heart healthy integrative nutritional counseling (H2INC): Creating a Chinese medicine + western medicine patient education curriculum for Chinese Americans. Issue 12 (December 2018) - Ho, Evelyn Y.; Acquah, Joseph; Chao, Cewin; Leung, Genevieve; Ng, Don C.; Chao, Maria T.; Wang, Abby; Ku, Shannon; Chen, Wanyi; Yu, Choi Kwun; Xu, Shuwen; Chen, Melissa; et al.
Highlights: Process of integrating western medicine and Chinese medicine as nutritional counseling. Integrative Nutritional Counseling (INC) fills void in health education. Chinese language nutrition education for preventative cardiovascular heart disease. Culturally-attuned clinical and preventive care for Chinese American patients. Abstract: Objectives: Current cardiovascular disease (CVD) nutrition guidelines do not take into account Chinese medicine (CM) principles. We created a heart healthy integrative nutritional counseling (H2INC) curriculum consistent with CM principles and current nutrition guidelines. Methods: We conducted three phases of semi-structured interviews with key stakeholders (CM and biomedical providers and Chinese American (CAs) patients with CVD) followed by iterative development of H2INC. First, we interviewed licensed CM providers (n = 9) and laypeople with CM foods expertise (n = 1). Second, we interviewed biomedical providers (n = 11) and licensed CM providers (n = 3). Third, we conducted four focus groups with CAs (n = 20) with CVD. Results: Stakeholders emphasized different principles for creating H2INC. Phase one emphasized alignment of CM diagnoses to biomedical CVD conditions. Phase two overlaid CM concepts like the nature of foods and constitution (hot/neutral/cool) with heart healthy nutrition recommendations such as MyPlate, and avoiding excess salt, fat, and sugars. Phase three demonstrated patient acceptability. Conclusion: By integrating CM foods principles with biomedical nutrition, this integrative approach yields culturally relevant health education for an underserved population. Practice Implications: Integrative nutritional counseling shows promise for CAs and could support biomedical providers with little knowledge about patients' use of CM for CVD.